2014
DOI: 10.1021/ja502780z
|View full text |Cite
|
Sign up to set email alerts
|

“Minimalist” Cyclopropene-Containing Photo-Cross-Linkers Suitable for Live-Cell Imaging and Affinity-Based Protein Labeling

Abstract: Target identification of bioactive compounds within the native cellular environment is important in biomedical research and drug discovery, but it has traditionally been carried out in vitro. Information about how such molecules interact with their endogenous targets (on and off) is currently highly limited. An ideal strategy would be one that recapitulates protein-small molecule interactions in situ (e.g., in living cells) and at the same time enables enrichment of these complexes for subsequent proteome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(156 citation statements)
references
References 39 publications
4
148
1
3
Order By: Relevance
“…Since the concept of the "minimalist linker" was rst introduced by Yao et al in 2013, 64 both a diazirine and a clickable moiety have been concurrently incorporated into a single alkyl chain (L 1-3 , Scheme 3). 64,65 This strategy has been demonstrated to be a remarkably efficient method for cmPAL and cell imaging. Very recently, a suite of "minimalist linkers" containing alkyldiazirine units and different bioorthogonal tags have been developed to nd targets of BRD4 inhibitors and obtain better insights into how a tag might affect the overall performance of a probe 66 (New).…”
Section: -63mentioning
confidence: 99%
“…Since the concept of the "minimalist linker" was rst introduced by Yao et al in 2013, 64 both a diazirine and a clickable moiety have been concurrently incorporated into a single alkyl chain (L 1-3 , Scheme 3). 64,65 This strategy has been demonstrated to be a remarkably efficient method for cmPAL and cell imaging. Very recently, a suite of "minimalist linkers" containing alkyldiazirine units and different bioorthogonal tags have been developed to nd targets of BRD4 inhibitors and obtain better insights into how a tag might affect the overall performance of a probe 66 (New).…”
Section: -63mentioning
confidence: 99%
“…To buck-up the missing tag, post-labeling approaches were developed by application of click chemistry. [60][61][62][63] A diol-type diazirine 48 was utilized to introduce an aldehyde by periodate oxidation followed by selective coupling with biotinyl hydrazide to detect trace amounts of labeled product. 64) Preinstalled alkylazide tag on 49 was substantially stable to the photolytic 65) The postlabeling approaches require, however, large excess reagents to complete enough tag on the labeled proteins existing very low concentrations.…”
Section: Follow-up Tagging After Photoaffinity Labelingmentioning
confidence: 99%
“…The authors have demonstrated their superiority to other methods with 12 kinase inhibitors. This strategy has also been further used in live-cell imaging and protein profiling (Li et al 2014c;Su et al 2015). Another approach to reduce the effect of linker addition is to include the linker beforehand in the small molecule; therefore, hit compounds generated from phenotypic screening already have a linker available for tagging or immobilization.…”
Section: Minimal and Integrated Affinity Probesmentioning
confidence: 99%